Taste of Home ultimate outdoor cookbook (Taste of Home Books, RDA Enthusiast Brands, LLC, 2025)
"Take your love of the outdoors to new heights when you dine outside! Whether you're grilling up a weeknight dinner on the deck, packing a picnic basket, planning a tailgate or contributing to the church potluck, Taste of Home's sensational new cookbook has you covered! This must-have collection features 394 dishes ideal for dining in the fresh air"--Page 4 of cover.